Integrated simulation framework for the impacts of large dams: Example of the GERD - Basheer, Mohammed; Siddig, Khalid; Elnour, Zuhal; Ahmed, Mosab O. M.; Ringler, Claudia (International Food Policy Research Institute, 2023)
Efficient water resources management is essential for the sustainable development of nations, and large dams are an important tool for achieving this endeavor. Here, we present an integrated approach to simulating the impacts of large dams, integrating river systems infrastructure, hydrodynamic, and economywide models. We apply the framework to examine the biophysical, GDP, and distributional impacts of the Grand Ethiopian Renaissance Dam (GERD) on Sudan.